PENGARUH WAKTU KONTAK AIR LINDI DAN UDARA TERHADAP LAJU KOROSI BAJA ST-41 DAN ST-60 - Muhammad Irfan Riyadi; Rudi Siswanto (Universitas Lambung Mangkurat, 2021)
The use of metals in the environment is especially important in environments such rubbish in heavy equipment or trucks, especially those of the tailgate is a tool to bring a variety of organic waste and inorganic bring the matter dissolved through a liquid called leachate and make contact or direct contact with the steel so that corrosion occurs due to leachate or wastewater flow contains many corrosive compounds that make part tailgate become quickly corroded. This study aims to determine the bias steel resist corrosion rate. The steel used is steel steel ST-41 and ST-60 is a low carbon steel and medium carbon steel. The methods used in research in the methods of losing weight and observe the types of corrosion that occurs by means of immersion with ASTM G31-72 which vary contact time for 3 weeks. Based on research conducted showed the corrosion rate of the fastest occur in steel ST-60 with a contact time of 1 week soaked the leachate and 2 weeks in contact with the air due to differences in the composition of the steel ST-60 and steel ST-41 which has a chromium content so high that steel ST-41 is superior in resisting corrosion rate while the type of corrosion that occurs is evenly corrosion and atmospheric corrosion.